Design and Simulation Research of Reciprocating Traction Drive Test Machine based on Virtual Prototype Technology - Chen Huitao; Gao Haichao; Chai Shanshan; Yan Fan; Sun Guangya (Jixie chuandong)
In order to solve the problem of the oil film traction transmission characteristic of the most of test machine under the transient condition can’t study at present in domestic,a test machine is designed to study the oil film traction transmission characteristic under transient condition. Then,a virtual prototype model of the reciprocating traction drive test machine is built by using Pro / E software,and the characteristics of kinematics and dynamics are studied,the characteristic curve of corresponding parameters is obtained. The results validated the correctness of the model,and the motion parameters and trajectory changing with the time of the reciprocating traction drive test machine is obtained. A certain reference for dynamics characteristic research of traction drive test machine under transient conditions is provided.